Vancomycin Presoaking of the Graft Appears to Prevent Infection After Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-analysis. Issue 1 (February 2022) - Figueroa, Francisco; Figueroa, David; Calvo, Rafael; Vaisman, Alex; Nuñez, Marilaura; Putnis, Sven
Background : Vancomycin presoaking of the graft has been shown to decrease infection rates in some case series of anterior cruciate ligament (ACL) reconstruction. Purpose : We sought to substantiate the efficacy of vancomycin presoaked grafts for the prevention of infection after ACL reconstruction. Methods : We performed a systematic review of Medline and OVID to assess the incidence of postoperative infection in studies comparing patients undergoing ACL reconstruction with the use of vancomycin presoaked ACL grafts and a control group of patients undergoing ACL reconstruction without the use of presoaked grafts. The efficacy of vancomycin presoaking was calculated using the Agresti-Coull confidence interval. Relative risk (RR) was calculated for every study and the total sample. Results : The 11 studies that met inclusion criteria comprised 24, 298 patients. In patients with vancomycin presoaking of the graft, 1 infection was reported in 8764 cases (0.01% rate). In the studies with control groups that did not have vancomycin presoaked grafts, there were 125 infections in 15, 534 ACL reconstructions (0.8% rate). The efficacy of vancomycin presoaking in preventing infection after ACL reconstruction was 99.9% (0.999%–1.000% CI). The overall RR obtained was 0.07 (0.03–0.16 CI). All included studies were retrospective cohort studies (level III). Conclusions : Vancomycin presoaking of the graft has been shown to decrease infection rates after ACL reconstruction in studies of low evidence level. This suggests the need for prospective randomized controlled trials addressing this issue so that recommendations on the routine use of vancomycin presoaking of ACL grafts can be made with confidence.